AKIBAT HUKUM PEMBATALAN AKTA NOTARIS PERIHAL PEMBENTUKAN PERHIMPUNAN PEMILIK DAN PENGHUNI SATUAN RUMAH SUSUN (PPPSRS) (Analisis Putusan Pengadilan Negeri Medan No.597/Pdt.G/2013/PN.Mdn) - RUTH MEYLANI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhd. Yamin2. Sunarmi3. T. Keizerina Devi A Building an apartment is an appropriate alternative in responding to theproblem of land acquisition for housing and residence. It is proper when anapartment has been resided then the owners or the residents should establish PPPSRS(Apartment Unit Owner and Resident Association) although, in practice, it can causelegal problems since the establishment is not based on the prevailing regulations. Theresearch problems are as follows: how about the establishment of PPPSRSCambridge, Medan, how about the legal consequence of the revocation of Notarialdeed on PPPSRS Cambridge, Medan, and how about the process of the revocation ofNotarial deed on PPPSRS Cambridge, Medan.Keywords: Legal Consequence, Revocation of Notarial Deed, Establishment,PPPSRS (Apartment Unit Owner and Resident Association)